Techno-Economic Analysis of Lanthanum Oxide Nanoparticles Production using Combustion Solution and Hydrothermal Supercritical Water Condition - Asep Bayu Nandiyanto; Irine Sofianty; Rofi Fadilah Madani; Adani Ghina Puspita Sari; Fitri Febriyanti; Risti Ragadhita; Rina Maryanti; Eddy Soeryanto Soegoto (Department Industrial Engineering, University of Muhammadiyah Malang, 2022)
Lanthanum oxide (La2O3) nanoparticles are widely applied in various fields and have the potential to be made on a fabrication scope. As a consequence, feasibility studies for generating industries for La2O3 production are required, particularly in developing countries. The purpose of this research was to evaluate and investigate the prospect of the production of La2O3 nanoparticles. This study was carried out to determine whether large-scale La2O3 production using solution combustion (SC) and hydrothermal supercritical water conditions (HSWC) is profitable or not. The analysis method was evaluated based on economic evaluation parameters such as gross profit margin, payback period, and cumulative net present value, while also taking technical aspects into account by designing commercial tools. An economic evaluation was made based on estimates of ideal conditions, such as tax increases, changes in raw materials, sales, workers' salaries, and utility costs. The results of the analysis show that the best method, and has great advantages, was the HSWC method. Based on an engineering perspective, this method produces 4.08 tons of La2O3 in 20 years of production. This study is expected to provide information on the production of La2O3 nanoparticles by comparing the solution combustion method and hydrothermal supercritical water conditions on an industrial scale.